(untitled) (Revista Brasileira de Contabilidade e Gestão, 2013)
Wi-Fi wireless networks are gaining more and more space over common wired networks due to their mobility and flexibility. To investigate this trend, this article describes a study of the use of wireless networks in the city of Ibirama-SC, analyzing and schematizing data such as: safety standards, arrangement of radio channels and standards used, brands of most used Wi-Fi Access Point devices, among others. This work presents the use of wardriving as a methodology for mapping the use of wireless networks in a given region.